PENGARUH SKEPTISISME PROFESIONAL, INDEPENDENSI, DAN TEKANAN ANGGARAN WAKTU PADA KUALITAS AUDIT - Harits Yodiantoro, HY (2021)
This study aims to determine the effect of professional skepticism, independence, and time budget pressure on audit quality on auditors working at KAP in DKI Jakarta listed in the directory 2021 KAP/AP. This research is a quantitative type of research using primary data in the form of a questionnaire distributed to auditors. the. The number of samples in this study amounted to 71 respondents and was selected by purposive sampling method. Data analysis using Structural Eqaution Modeling (SEM) with SmartPLS version 3.0 software. The results of this study conclude that professional skepticism has a significant effect on quality. Independence and time budget pressure can not affect the quality of the audit.